RESPON SETEK TUMBUHAN RAMBUSA (Passiflora foetida L) TERHADAP KONSENTRASI DAN WAKTU PERENDAMAN ZAT PENGATUR TUMBUH (ZPT): RESPONSE OF RAMBUSA (Passiflora foetida L) CUTTINGS TO CONCENTRATION AND IMMERSION TIME OF GROWTH REGULTING SUBSTANCES (PGR) - Hamidah; Jededius Jenau (Agrifarm : Jurnal Ilmu Pertanian, 2021)
Passiflora foetida L, better known as rambusa, grows in plantation areas, meadows, roadsides and vacant land. Rambusa is a plant that has not been widely used by the community. Rambusa plant (Passiflora foetida L) has various benefit, including s a medicine to treat bones, anemia, cancer, blood pressure, gums and teeth, kidney disorders, and stress. The part used in the rambusa plant is the fruit. The rambusa fruit contains calcium, iron, antioxidants, minerals and also vitamin C. Growth regulators (ZPT) are natural or synthetic organic compounds that promote, inhibit or modity qualitatively the growth and development of plants. Growth regulatrs play an important role in controlling biological processes in plat tissues. The aim of the study was to determine the effect of the concentration and duration of immersion in the appropriate ZPT for rambusa plants. The research was carried out on Jalan Pramuka, Gunung Kelua Village, Samarinda Ulu District, East Kalimantan for 3 (three) months starting from September 1 to Desember 1, 2021. The study was arranged in a Completely Randomized Design (RAK) with 2 factors 3 replications, namely : The first factor is the Concentration of ZPT Root Most (R) which consists of 3 (three) levels, namely : R0: Without PGR; R1 : 2 ml L-1. ; R2 ; 4 ml L-1. The second factor is the length of immersion (P) which consists of 3 (three) levels, namely : P0; No Immersion; P1: Immersion 90 minutes; P2 : Immersion 180 minutes. Research parameters, among other; Calculating the Percentage of Live Seeds; Plant length and number of shoots will be counted at 4, 8 and 12 weeks after planting. The results showed that the concentration treatment of Root Most R1 2 ml L-1 had a significant effect on the parameters of plant length 12 weeks after planting, which was 106.03 cm. Treatment duration of immersion P1: immersion 90 minutes gave a significant effect on the parameters of plant length 12 weeks after planting, which was 102.11 cm